Transformation Model and Systematic Approach for Smart Maritime Logistics: A Literature Analysis - Azisah, Nur; Karim Ladesi, Vivian; Mulyono, Tri; Puspa Wangi, Intan; Paotonan, Chairul (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
This article examines advanced technology applications in maritime logistics through a systematic literature review and bibliometric analysis. Using established PRISMA guidelines, 72 relevant articles were selected from major academic databases and analyzed using bibliometric tools to identify research trends and key findings. The research identifies how Internet of Things (IoT), artificial intelligence (AI), blockchain, and automation technologies enhance operational efficiency and environmental sustainability in maritime logistics. Results demonstrate that these technologies improve supply chain visibility and control while reducing greenhouse gas emissions and energy consumption. The analysis reveals that IoT enables real-time monitoring, AI supports intelligent decision-making, blockchain enhances transparency and security, and automation reduces manual workload. Environmental sustainability emerges as a key focus, with technologies optimizing port operations and minimizing environmental impact. This research emphasizes the need for a holistic approach to smart maritime logistics that integrate technology, management, and sustainability. The findings contribute to academic literature and provide practical insights into the maritime industry’s adoption of advanced technologies to achieve improved operational efficiency and sustainability.